2015
DOI: 10.1016/j.jdiacomp.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Predicting non-diabetic renal disease in type 2 diabetic adults: The value of glycated hemoglobin

Abstract: This study demonstrated a considerably high prevalence of NDRD in T2D adults undergoing renal biopsy. The absence of diabetic retinopathy, lower HbA1c values 12 months before biopsy and greater deterioration in HbA1c prior to biopsy predicted NDRD in T2D. Further studies are needed to validate the findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…In a retrospective study of 51 T2DM patients, Pallayova et al showed that 35 (68.6%) patients had non-diabetic etiology. The most common diagnoses were interstitial nephritis (20%), progressive crescentic glomerulonephritis (14%), MN (11%) and FSGS (11%) [24]. In our study, according to the kidney biopsy findings, pure NDKD was detected in 50% of the patients.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In a retrospective study of 51 T2DM patients, Pallayova et al showed that 35 (68.6%) patients had non-diabetic etiology. The most common diagnoses were interstitial nephritis (20%), progressive crescentic glomerulonephritis (14%), MN (11%) and FSGS (11%) [24]. In our study, according to the kidney biopsy findings, pure NDKD was detected in 50% of the patients.…”
Section: Discussionmentioning
confidence: 52%
“…Prakash and colleagues observed NDKD in 40% of cases with DR and DKD in 43% of the cases without DR, which suggested that the lack of DR did support NDKD, but it did not exclude DKD [16]. Pallayova and colleagues demonstrated that the predictors of NDKD in T2DM patients were absence of DR, lower HbA1c values 12 months before biopsy and greater deterioration in HbA1c prior to biopsy [24]. In our study, DR was found in 18 (37.5%) patients; 15 (75%) in the isolated DKD patient group, 2 (8.3%) in the isolated NDKD patient group, and 1 (25%) in the DKD+NDKD patient group.…”
Section: Discussionmentioning
confidence: 99%
“…However, it can sometimes be diffi cult to estimate exactly how long diabetes has been present as type 2 diabetes can remain asymptomatic for a number of years. The likelihood of nephropathy is greater if there has been a long period of poor glucose control [ 3 ].…”
Section: Is It Diabetic Nephropathy ?mentioning
confidence: 99%
“…Patients with diabetic nephropathy almost always have retinopathy [ 3 ] and often have cardiovascular or peripheral vascular disease.…”
Section: Is There Proteinuria or Haematuria?mentioning
confidence: 99%
“…As both of these parameters were separately predictive of non-diabetic etiology, the authors proposed a model based on the interaction between these two terms and which predicted non-diabetic etiology with 73.7% sensitivity and 75% specificity (AUC, 0.77; 95% CI, 0.59 to 0.94) (Pallayova et al, 2015). The study demonstrates that when carefully selected, diabetic patients with features atypical of DN have a high probability of having a non-diabetic etiology, but it remains to be seen if this model will work prospectively with comparable degree of sensitivity and specificity in predicting NDRD with in diabetics.…”
mentioning
confidence: 99%